"It's the Way That You Do It": Developing an Ethical Framework for Community Psychology Research and Action. Issue 3 (28th April 2016) - Campbell, Rebecca
Abstract: In the 50 years since the 1965 Swampscott conference, the field of community psychology has not yet developed a well‐articulated ethical framework to guide research and practice. This paper reviews what constitutes an "ethical framework"; considers where the field of community psychology is at in its development of a comprehensive ethical framework; examines sources for ethical guidance (i.e., ethical principles and standards) across multiple disciplines, including psychology, evaluation, sociology, and anthropology; and recommends strategies for developing a rich written discourse on how community psychology researchers and practitioners can address ethical conflicts in our work.